Strategi Dinas Pemberdayaan Masyarakat dan Desa Provinsi Sumatera Barat dalam Pendampingan Nagari untuk Pelaksanaan Aplikasi Indeks Desa Membangun - Olivia Dwi Ruselda; Yulia Hanoselina (Al-DYAS, 2026)
The Indeks Desa Membangun (IDM) is a strategic government instrument for measuring village independence and development based on social, economic, and environmental dimensions; however, the use of the IDM Application in West Sumatra Province still faces various challenges that affect data quality and the effectiveness of village development planning. This study aims to analyze strategies for improving the use of the Indeks Desa Membangun (IDM) Application and to identify the constraints encountered in its implementation at the Dinas Pemberdayaan Masyarakat dan Desa Provinsi Sumatera Barat. The research employed a qualitative approach with a descriptive method, involving purposively selected informants who understand and are directly involved in the management and implementation of IDM. Data were collected through in-depth interviews, observations, and document analysis, then qualitatively analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that efforts to enhance IDM have been pursued through technical assistance, capacity building for government apparatus, and optimization of digital systems, but these strategies have not yet functioned optimally. The main constraints include limited understanding among village officials, low participation of village governments and communities, gaps in information technology infrastructure, ineffective coordination across levels of government, and the predominantly administrative use of IDM data, which has not yet fully served as a basis for policy making. The study concludes that the success of strategies to strengthen the IDM Application requires enhanced human resource capacity, improved technological infrastructure, stronger institutional coordination, and the consolidation of IDM data utilization as the foundation for data-driven village development planning in West Sumatra Province.